Importance of Carbon Contamination in High-Resolution (FEG) EPMA of Silicate Minerals. (16th April 2015) - Buse, Ben; Kearns, Stuart
Abstract: The effect of carbon contamination on the analysis of carbon-coated silicate minerals at 5 kV for X-ray energies 0.7–4 keV is examined. For individual spot analyses, carbon is found to deposit adjacent to the beam spot forming ring-shaped deposits with no impact on the analysis. Carbon contamination becomes important for closely spaced analyses such as multipoint transects, where each subsequent analysis overlaps the carbon ring of the previous analysis. X-ray intensity loss due to contamination is most severe for low-overvoltage elements such as Ca K consistent with carbon deposition effectively reducing beam energy. Rates of contamination are calculated and the use of a liquid nitrogen cold trap is shown to greatly reduce the amount of carbon deposited. A complimentary empirical correction is developed to correct for X-ray intensity loss from measured carbon, assuming the carbon is a film, and is compared with corrections derived from thin film calculations. PENELOPE electron probe microanalysis (PENEPMA) calculations confirm that asymmetry of the carbon deposition can be ignored for X-ray energies where intensity loss is predominantly through energy loss of beam electrons. Using a cold trap and/or an empirical correction high spatial resolution analysis (ca. 400 nm between points) is achievable with analytical errors of ca. 1–3%.